(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2014)
This paper presents an application to authenticate incoming call receiver, based on robust and fast face recognition engine. The application allows registering and verifying subjects by storing and comparing their biometric information respectively. Application restricts the user to receive incoming call unless it verifies the proposed entity, if the entity is authentic then call will be received else application will reject the call automatically. All the processing is done in mobile device. Face recognition is based on Local Binary Patterns (LBP) features, which have shown to be a powerful and computationally efficient feature extractor. The algorithm constitutes the engine of a new face recognition based user authentication for incoming call application. In terms of convenience, a higher degree of user-friendliness can be achieved if the biometric authentication is transparent, which means that the authentication can be done without explicit user actions. The current application runs on Android O.S., having been tested in mobile platform, demonstrating the feasibility of the proposed approach.